The gas-star formation cycle in nearby star-forming galaxies: II. Resolved distributions of CO and alpha emission for 49 PHANGS galaxies - Pan, Hsi-An; Schinnerer, Eva; Hughes, Annie; Leroy, Adam; Groves, Brent; Barnes, Ashley Thomas; Belfiore, Francesco; Bigiel, Frank; Blanc, Guillermo A.; Cao, Yixian; Chevance, Mélanie; Congiu, Enrico; et al. (The astrophysical journal, 2022)
The relative distribution of molecular gas and star formation in galaxies gives insight into the physical processes and timescales of the cycle between gas and stars. In this work, we track the relative spatial configuration of CO and Hα emission at high resolution in each of our galaxy targets and use these measurements to quantify the distributions of regions in different evolutionary stages of star formation: from molecular gas without star formation traced by Hα to star-forming gas, and to H ii regions. The large sample, drawn from the Physics at High Angular resolution in Nearby GalaxieS ALMA and narrowband Hα (PHANGS-ALMA and PHANGS-Hα) surveys, spans a wide range of stellar masses and morphological types, allowing us to investigate the dependencies of the gas‒star formation cycle on global galaxy properties. At a resolution of 150 pc, the incidence of regions in different stages shows a dependence on stellar mass and Hubble type of galaxies over the radial range probed. Massive and/or earlier-type galaxies in our sample exhibit a significant reservoir of molecular gas without star formation traced by Hα, while lower-mass galaxies harbor substantial H ii regions that may have dispersed their birth clouds or formed from low-mass, more isolated clouds. Galactic structures add a further layer of complexity to the relative distribution of CO and Hα emission. Trends between galaxy properties and distributions of gas traced by CO and Hα are visible only when the observed spatial scale is ≪500 pc, reflecting the critical resolution requirement to distinguish stages of the star formation process.